Formation and Properties of TiSi2 as Contact Material for High-Temperature Thermoelectric Generators - Assion, Fabian; Schönhoff, Marcel; Hilleringmann, Ulrich (MRS Proceedings)
ABSTRACT Thermoelectric generators (TEG) are capable of transforming waste heat directly into electric power. With higher temperatures the yield of the devices rises which makes high-temperature contact materials important. The formation of titanium disilicide (TiSi 2 ) and its properties were analyzed and optimized for the use in TEG. Depending on a direct or an indirect transformation into the C54 crystal structure the process forms a layer with a resistivity of 20-22 μΩcm. Process gases influence the resistivity and result in difference of 20 %. The growing rate of TiSi 2 on silicon dioxide was determined; it shows a strong dependence on the used atmosphere and temperature. A maximum overgrowing length of 30 μm was found.
Keywords: General Engineering

Design and implementation of a measurement system for automatically measurement of electrical parameters of thermoelectric generators - Petrov, Dmitry; Assion, Fabian; Hilleringmann, Ulrich (MRS Proceedings)
ABSTRACT The continues development of thermoelectric generators causes a permanent improvement of their characteristics. New types of thermoelectric generators can work at temperatures up to 1000 K. With this, special measurement equipment is needed to control the electrical parameters of the new developed specimens. The devices must be tested over the whole range of operating temperatures. For each temperature value a series of electrical measurements has to be performed. To establish the maximal output power of the thermoelectric generators, a load resistor with variable resistance has to be connected to the output of thermoelectric generator. The measurement system should measure the electrical current through the load resistor and the voltage over this resistor to determine the device parameters. A large amount of measurement data have to be collected and processed to evaluate the electrical characteristics of the specimen and to present them in graphical form, suitable for the comparison with others specimens.
Keywords: General Engineering

Optical properties of GaN photonic crystal membrane nanocavities at blue wavelengths - Choi, Y.-S.; Meier, Cedrik; Sharma, R.; Hennessy, K.; Haberer, E. D.; Nakamura, S.; Hu, E. L.

Synthesis and Al K-Edge Xanes Investigation of Mesostructured Aluminophosphates - Tiemann, Michael; Fröba, M.; Wong, J. (MRS Proceedings)
We report on the synthesis of lamellar mesostructured aluminophosphate composites which contain variable relative amounts of aluminium oxide species in the core regions of the lamellae; this is investigated quantitatively by Al K-edge XANES spectroscopy. Templating is achieved by the utilisation of monododecyl phosphate surfactant. If no phosphorous source (such as H3PO4) is used for the synthesis, the phosphate head groups of the surfactant become incorporated into the inorganic network to form similar lamellar aluminophosphate structures. Thus, the surfactant serves as both template and reactant.